Strategi Penguatan Moral Siswa di Sekolah (Study Deskriptif Tentang Penguatan Nilai Moral Siswa Melalui Program Sekolah di SD Islam Terpadu Al-Madaniyah Samuda) - Mutaqin Saufi; Musyorofah Musyorofah; Ali Sibram Malisi (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2023)
This study aims to examine how strategies strengthen student morale through school programs. In analyzing the problem, this research uses descriptive method with observation, interview and documentation techniques. Some of the findings obtained from research that the strategy of strengthening students' morale is implemented in several aspects; firstly on the school's vision and mission where the school compiles the school's vision-mission and goals which imply faith, piety and religious values ​​to strengthen student morale, second on activities both habituation activities within the school environment or activities outside the school environment related to religious activities to increase religious values, third on school facilities and infrastructure, fourth on school rules which are arranged based on the school's vision-mission and goals. The research results show that the strategy is quite successful in strengthening student morale. There are several findings that can hinder the success of applying student moral values, such as: the number of students that is not balanced with the number of classes, the lack of optimal use of facilities, the lack of commitment from school members, especially the lack of parental cooperation in efforts to strengthen student morale.